Hubungan Pengetahuan dan Sikap dengan Pemanfaatan Sumberdaya Hayati Laut Untuk Kesehatan Masyarakat Pesisir Kecamatan Soropia - I Putu Sudayasa; Ratih Harlyan Lawenga (Halu Oleo University, 2016)
The level of biodiversity in Indonesia as a tropical country is very high, the potential of marine biological resource makes the sea of Indonesia called as Marine Mega-Biodiversity region in the world. Therefore it was expected especially in coastal communities can take and utilizing of marine biological resource optimally, especially for conventional and traditional for health. However basical knowledge and attitude of coastal communities about coastal and marine resources primarily for its management is still lack. The lack of the basical knowledge can affect the inability of society to engage in the use of coastal and marine resources, especially the utilization of marine biological resources in health. The aim of this research was to determine the relationship between knowledge and attitude to the utilization of marine biological resource for health on coastal communities area of Soropia wich one of coastal areas in Southeast Sulawesi with high potential of marine biological resorces. The research method used observational design with cross sectional approach. The subjects of the research were coastal communities in Soropia located in three villages, namely Tapulaga, Leppe and Bajoe. This research was conducted for January 2016, with 292 respondents of population. The sample were selected by using stratified random sampling technique that obtained 167 respondents. Bivariate analysis was performed by Chi square and Fisher test.The result of bivariate analysis showed that there was significant relationship between knowledge (p=0,000) and the utilization of marine biological resource for health and there was significant relationship between attitude (p=0,014) and the utilization of marine biological resource for health. This research concluded that there were significant relationship between knowledge and attitude to the utilization of marine biological resource for health in the coastal community area of Soropia. The present research suggested that there would be further research that investigated the efficacy of Enhalus acoroides root as the alternative treatment to resolve Diabetes disease, Semele cordiformis as the alternative medication to cure Hepatitis disease and Siganus sp. bile as the alternative analgesic medication to wounds caused by fish bone.Keywords: marine biological resource,health, knowledge, attitude, coastal community